THE USE OF COMIC FIGURES TO DEVELOP STUDENTS’ SPEAKING SKILL - Diyansyah, Harno (unwir press, 2017)
English is an international language that is the language for science, businesscommunication, and technology. Many scientific books are written in English .But infact learning English as second language still became a problem for us. This might becaused by the differences between English language and Indonesian languageespecially in communication each other. Basically, there are four skills required inEnglish teaching learning program. They are reading, speaking, listening and writing.Base on those skill, speaking is one of the most important skill in language learning.By speaking, we can convey information and ideas, and maintain social relationshipby communicating with others. By speaking people make interaction betweenindividual and community. The writer tried to use comic figure as media to developstudent in speaking skill, the reason is because every comic figures have strangecharacter, identity, and habitually who inspirited and influence many students. Comicfigures are fun media to make students interest in learning English especially inspeaking subject. Comic figure may usual media, but comic figure made is because thedeveloper has massage whom want to tells to everyone. Then the writer discus andanalyzed base on result of research to answer research question. These researchesdiscuss the English (speaking context) in classroom using comic figures and thestudents? activity and responses toward comic figures. This research also to improvethe writer and students trough post-test (for the students). The last is chapter isexplained about the result of research, conclusion. The result indicates that there weremany positive progress toward students? speaking score as the answer of formulationof the problem, students activity and teacher (researcher) behaviors. It was proven bythe increase of students speaking score and class average score. The use of comicfigures to develop students speaking skill was getting positive responses and able todevelop students speaking skill. The last, the writer hope the use of comic figures willgive contribution to solve the problem on learning process